REPLACEMENT OF A MAXILLARY CENTRAL INCISOR USING A POLYETHYLENE FIBER-REINFORCED COMPOSITE RESIN FIXED PARTIAL DENTURE: A CLINICAL REPORT - (:unkn) unknown (MOSBY-ELSEVIER, 2008)
Fiber-reinforced composite resin (FRC) restorations generally consist of a composite resin veneer supported by a fiber-reinforced composite resin substructure and prepared chairside to be used when the patient needs a short-term solution. It is an esthetic, conservative treatment alternative and allows for future options. This article describes the use of a polyethylene fiber-reinforced composite resin fixed partial denture (PFRCFPD) with a ceramic pontic for the replacement of a missing central incisor due to trauma. (J Prosthet Dent 2008;100:254-258)
Keywords: CERAMIC SURFACE; BOND STRENGTH; PROSTHESES; PORCELAIN; DESIGN